2-Methoxyestradiol Attenuates Angiotensin II-Induced Hypertension, Cardiovascular Remodeling, and Renal Injury. Issue 3 (March 2019) - Salah, Eman; Bastacky, Sheldon I.; Jackson, Edwin K.; Tofovic, Stevan P.
Abstract : Abstract: Estradiol may antagonize the adverse cardiovascular effects of angiotensin II (Ang II). We investigated the effects of 2-methoxyestradiol (2-ME), a nonestrogenic estradiol metabolite, on Ang II-induced cardiovascular and renal injury in male rats. First, we determined the effects of 2-ME on Ang II-induced acute changes in blood pressure, renal hemodynamics, and excretory function. Next, we investigated the effects of 2-ME and 2-hydroxyestardiol (2-HE) on hypertension and cardiovascular and renal injury induced by chronic infusion of Ang II. Furthermore, the effects of 2-ME on blood pressure and cardiovascular remodeling in the constricted aorta (CA) rat model and on isoproterenol-induced (ISO) cardiac hypertrophy and fibrosis were examined. 2-ME had no effects on Ang II-induced acute changes in blood pressure, renal hemodynamics, or glomerular filtration rate. Both 2-ME and 2-HE reduced hypertension, cardiac hypertrophy, proteinuria, and mesangial expansion induced by chronic Ang II infusions. In CA rats, 2-ME attenuated cardiac hypertrophy and fibrosis and reduced elevated blood pressure above the constriction. Notably, 2-ME reduced both pressure-dependent (above constriction) and pressure-independent (below constriction) vascular remodeling. 2-ME had no effects on ISO-induced renin release yet reduced ISO-induced cardiac hypertrophy and fibrosis. This study shows that 2-ME protects against cardiovascular and renal injury due to chronic activation of the renin–angiotensin system. This study reports for the first time that in vivo 2-ME reduces trophic (pressure-independent) effects of Ang II and related cardiac and vascular remodeling.